2003
DOI: 10.1057/palgrave.mel.9100072
|View full text |Cite
|
Sign up to set email alerts
|

Applying Maritime Economics to Set Foundations for Port and Shipping Policies

Abstract: This special edition of MEL features a selection of outstanding papers that were presented during the event. 1 Under the conference theme 'Maritime Economics -setting the foundations for port and shipping policies', the organisers aimed to encourage papers which are of particular interest to the public sector and policy-makers. Topics such as shipping alliances, the regulation of ports, the economic impact of transport corridors, future intermodal and transshipment patterns, and the relationship between tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Transport policy as a whole is ultimately about choices policymakers make concerning investment, subsidies and taxes that affect different transport modes (Hoffmann, 2003). This means the economic, environmental and social impacts of maritime transport have to be estimated, and these estimates need to be incorporated into trade and transport forecasts, which should then help to determine the allocation of public resources and policy mechanisms.…”
Section: A R I T I M E P O L I C Ymentioning
confidence: 99%
See 1 more Smart Citation
“…Transport policy as a whole is ultimately about choices policymakers make concerning investment, subsidies and taxes that affect different transport modes (Hoffmann, 2003). This means the economic, environmental and social impacts of maritime transport have to be estimated, and these estimates need to be incorporated into trade and transport forecasts, which should then help to determine the allocation of public resources and policy mechanisms.…”
Section: A R I T I M E P O L I C Ymentioning
confidence: 99%
“…The United Nations Conference on Trade and Development suggested that the goals of a maritime policy should be (Hoffmann, 2003):…”
Section: A R I T I M E P O L I C Ymentioning
confidence: 99%